Determination of metals and pharmaceutical compounds released in hospital wastewater from Toluca, Mexico, and evaluation of their toxic impact. (September 2018) - Pérez-Alvarez, Itzayana; Islas-Flores, Hariz; Gómez-Oliván, Leobardo Manuel; Barceló, Damià; López De Alda, Miren; Pérez Solsona, Sandra; Sánchez-Aceves, Livier; SanJuan-Reyes, Nely; Galar-Martínez, Marcela
Abstract: Due to the activities inherent to medical care units, the hospital effluent released contains diverse contaminants such as tensoactives, disinfectants, metals, pharmaceutical products and chemical reagents, which are potentially toxic to the environment since they receive no treatment or are not effectively removed by such treatment before entering the drain. They are incorporated into municipal wastewater, eventually entering water bodies where they can have harmful effects on organisms and can result in ecological damage. To determine the toxicological risk induced by this type of eflluents, eight metals and 11 pharmaceuticals were quantified, in effluent from a hospital. Developmental effects, teratogenesis and oxidative stress induction were evaluated in two bioindicator species: Xenopus laevis and Lithobates catesbeianus . FETAX (frog embryo teratogenesis assay– Xenopus ) was used to obtain the median lethal concentration (LC50 ), effective concentration inducing 50% malformation (EC50 ), teratogenic index (TI), minimum concentration to inhibit growth (MCIG), and the types of malformation induced. Twenty oocytes in midblastula transition were exposed to six concentrations of effluent (0.1, 0.3, 0.5, 0.7, 0.9, 1%) and negative and positive (6-aminonicotinamide) controls. After 96 h of exposure, diverse biomarkers of oxidative damage were evaluated: hydroperoxide content, lipid peroxidation, protein carbonyl content, and the antioxidant enzymes superoxide dismutase and catalase. TI was 3.8 in X. laevis and 4.0 in L. catesbeianus, both exceed the value in the FETAX protocol (1.2), indicating that this effluent is teratogenic to both species. Growth inhibition was induced as well as diverse malformation including microcephaly, cardiac and facial edema, eye malformations, and notochord, tail, fin and gut damage. Significant differences relative to the control group were observed in both species with all biomarkers. This hospital effluent contains contaminants which represents a toxic risk, since these substances are teratogenic to the bioindicators used. The mechanism of damage induction may be associated with oxidative stress. Graphical abstract: Image Highlights: Hospital effluent had eight metals and eleven drugs, toxic to the environment. This effluent was teratogenic to Xenopus laevis and Lithobates catesbeianus. Growth inhibition was induced by the effluent in the frogs studied. Main malformations found were microcephaly, cardiac and facial edema, and axials. The mechanism of teratogenesis may be associated with oxidative stress. Abstract : Hospital effluent induces embryotoxicity and teratogenesis in Xenopus laevis and Lithobates catesbeianus, and has an ecological impact.